Nucleotides and Saccharide Synthesis (Versión 1) - Leloir, Luis Federico (1957)
Versión publicada: Leloir, Luis F. “Nucleotides and Saccharide Synthesis”. EN: Polysaccharides in Biology. Transactions of the Third Conference on Polysaccharides in Biology, Josiah Macy Jr. Foundation. New York: Springer, 1958.